SINTESIS DAN KARAKTERISASI EKSTRAK DAUN NAMNAM SEBAGAI ANTIMIKROBA - Rachmawati, Nurmeily; Syarah Anliza; Dian Pratiwi; Digna Renny Panduwati (Jurnal Medikes (Media Informasi Kesehatan), 2025)
The biodiversity owned by a country is a gift that must be appreciated. The potential of these natural resources can be used as research material to overcome existing problems. One of them is about how to answer the challenges of the effects caused by the use of chemicals that can harm the environment and surrounding living things. Therefore, it is necessary to modify the use of chemicals to be more optimal and of course safe both in use and effects. Modification of the particle size of a substance provides benefits because the size of a substance becomes smaller (nanoparticles) so that it will expand the surface of the contact substance. Several applications of the use of nanoparticles of a substance as a drug target carrier agent, sensor, increased bioavailability, and reduced effects of a substance have been carried out by several researchers. This study aims to evaluate the continuation of the potential of namnam leaves which have quite good bioactivity as antimicrobials. The method used is laboratory experimental. The research stages include the manufacture of namnam leaf extract, phytochemical test of the extract, and antimicrobial activity test. The extract was made by maceration using methanol for 3x24 hours and produced a yield of 11.2%. The results of the phytochemical test showed that the methanol extract of namnam leaves contains active compounds such as flavonoids, saponins, phenolics, steroids, and tannins. The content of these active substances has the potential as antimicrobials. The preliminary bioactivity test was carried out using the well method which produced inhibition zones of 15 mm, 18 mm, and 18 mm. The value of this inhibition zone is included in the sensitive category according to the CLSI data division.